PENGARUH PERSEPSI KEGUNAAN QRIS DAN KEMUDAHAN QRIS TERHADAP EFISIENSI PEMBAYARAN DIGITAL PADA SISWA - Kurniasih Setyagustina, Kurniasih Setyagustina; Iis Dahlia; Ahmadi; Winahyu Dwi Suhitasari; Wahyudil Khotib; Iyud (Moneta: Jurnal Manajemen & Keuangan Syariah, 2024)
Use of QR code for transaction payment moment This Still not enough known by the public . one influencing factors the use of the Quick Response Code Indonesian Standard (QRIS) is factor risk , promotion , referrals , and others. Study This aim For know influence the benefits of QRIS, the convenience of QRIS, and efficiency digital payment Quick Response Code Indonesian Standard (QRIS) for students faculty economy and business Islamic religious institute sheik maulana qori bank . The sample used is as many as 100 respondents , method research used _ is method quantitative with analysis regression multiple , and technique data collection is carried out with method spread questionnaire. Technique processing and analysis of data namely , instrument test , assumption test classic , analysis regression multiple and hypothesis test . Research results show that : (1) There is influence variable Benefits of QRIS against Efficiency Digital Payments online partial . Can seen from that t test variable This obtain t value count before sar 4.269 > 1.988 and value significant of 0.000 <0.05. (2) exists influence variable Ease of QRIS against Efficiency Digital Payments online partial. Got seen from that t test variable This obtain t value count of 6.538 > 1.988 and value significant of 0.000 <0.05 (3) Research results this also proves variable Benefits of QRIS and Ease of QRIS simultaneous own influence to Efficiency Digital Payments . this _ can seen from calculated F value obtained _ of 96.947 > F table 2.70 and value significant of 0.000 <0.05. Based on explanation on so writer give recommendation to the IAI SMQ Bangko campus , the FEBI faculty so that you can more intense Again For educate student about development technology digital payments (QRIS) so the goal of launching QRIS was achieved .